HBR guide to better business writing - Garner, Bryan A. (Harvard business review guides, 2012)
The HBR Guide to Better Business Writing, by writing expert Bryan A. Garner, gives you the tools you need to express your ideas clearly and persuasively so clients, colleagues, stakeholders, and partners will get behind them. This book will help you:• Push past writer’s block. • Grab—and keep—readers’ attention. Earn credibility with tough audiences. • Trim the fat from your writing. • Strike the right tone.